Intensity Modulated Radiotherapy is an Effective Treatment for Basosquamous Cell Cancer - Rolina K. Al-Wassia (Journal of King Abdulaziz University: Medical Sciences, 2023)
Basosquamous cell carcinoma is an uncommon skin cancer with an incidence rate between 1.5% and 2.7%. Surgical excision is the therapy of choice for most skin neoplasm. Depending on the tumor presentation size, location, and patient general condition, there are complementary approaches available: radiation therapy, for curative intent or used as an alternative to maximize local control and symptomatic relief. The case is a 54-year-old male with a seventeen year history of six times recurrent Basosquamous cell cancer that started as a skin nodule on the left nasolabial fold and ended with a mass penetrating into the left ethmoid sinus and orbital cavity. The patient was then treated using intensity modulated radiotherapy as the only effective second alternative modality after debulking surgery. Radiation intent was curative, aiming for eradication of the tumor, maximizing the local control and relief of symptoms. The follow-up demonstrated an eighty percent tumor shrinkage as measured on imaging studies in addition to an excellent cosmetic outcome. Intensity modulated radiotherapy proved to be an efficient treatment modality, with acceptable toxicity and excellent local control, when the patient did not prefer the surgical option for the cosmetic compromise.